Molli Maulwurf und das Dideldudelding - Jörg, Sabine 1948- (Schneider, 1988)
The meadow was a nice place to live, but the smaller animals were ignored by the big cows. Molli the mole thought of a way to get their attention by inventing the Dideldudelding.
Keywords: Cows -- Fiction; German language materials; Meadow animals -- Fiction; Moles (Animals) -- Fiction